Advancements in nanotechnology for the diagnosis and treatment of multiple myeloma. (11th August 2020) - Zhong, Wenhao; Zhang, Xinyu; Zhao, Meng; Wu, Jun; Lin, Dongjun
Abstract : Multiple myeloma (MM), known as a tumor of plasma cells, is not only refractory but also has a high relapse rate, and is the second-most common hematologic tumor after lymphoma. Abstract : Multiple myeloma (MM), known as a tumor of plasma cells, is not only refractory but also has a high relapse rate, and is the second-most common hematologic tumor after lymphoma. It is often accompanied by multiple osteolytic damage, hypercalcemia, anemia, and renal insufficiency. In terms of diagnosis, conventional detection methods have many limitations, such as it is invasive and time-consuming and has low accuracy. Measures to change these limitations are urgently needed. At the therapeutic level, although the survival of MM continues to prolong with the advent of new drugs, MM remains incurable and has a high recurrence rate. With the development of nanotechnology, nanomedicine has become a powerful way to improve the current diagnosis and treatment of MM. In this review, the research progress and breakthroughs of nanomedicine in MM will be presented. Meanwhile, both superiorities and challenges of nanomedicine were discussed. As a new idea for the diagnosis and treatments of MM, nanomedicine will play a very important role in the research field of MM.